2020
DOI: 10.1136/gutjnl-2020-322026
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sutured gastroplasty in addition to lifestyle modification: short-term efficacy in a controlled randomised trial

Abstract: ObjectiveEndoscopic suture gastroplasty (ESG) has been developed as an alternative treatment for moderately obese patients. We present our results of a short-term randomised controlled trial on a new suturing technique, the Endomina system (E-ESG, Endo Tools therapeutics, Belgium).DesignEligible patients (body mass index 30–40 kg/m2) were randomised in a 2:1 ratio to receive lifestyle modification plus E-ESG or lifestyle modification alone (control group); dietetic counselling and follow-up were identical. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In addition, the quality of life was significantly better in the Endomina group than in the control group (52.8% vs. 42.1%). No serious adverse events were recorded during the trial [40].…”
Section: Endoscopic Sleeve Gastroplasty (Esg)mentioning
confidence: 99%
“…In addition, the quality of life was significantly better in the Endomina group than in the control group (52.8% vs. 42.1%). No serious adverse events were recorded during the trial [40].…”
Section: Endoscopic Sleeve Gastroplasty (Esg)mentioning
confidence: 99%
“… 63 65 Other over the scope suturing devices, such as Endomina (Endo Tools Therapeutics, Brussels) have since come on the market, however has primarily used in endoscopic suture gastroplasty. 66 , 67 A retrospective, single-centre study, showed promising results of colonic closures with suturing devices. Of 21 patients with iatrogenic colonic perforations 5 (24%) were closed with TTSCs and 16 (76%) with an endoscopic suturing device.…”
Section: Endoscopic Suture Devicesmentioning
confidence: 99%
“…Although the sample size is small in this study, it showed that quality of life and weight loss improve dramatically when ESG with Endomina system is used along with lifestyle modifications. 82 …”
Section: Society Guidelinesmentioning
confidence: 99%
“…Although the sample size is small in this study, it showed that quality of life and weight loss improve dramatically when ESG with Endomina system is used along with lifestyle modifications. 82 In June 2019, a consensus meeting of 47 endoscopists experienced in ESG with 1828 procedures was held in Brazil. The published results of this study showed a TBWL of 18.2% in 1 year.…”
Section: Botulinum Toxin a Recent Reports Have Suggested That Botulinum Toxin A (Btx-a) Can Help Losementioning
confidence: 99%